Method of revealing indications for surgical treatment of posttraumatic extension contractions of the knee joint - Barkov, Alexandr; Barkov, Aleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The diagnosis of «persistent extensor contracture of the knee joint» is established only when it is impossible to eliminate conservatively for a certain time. Objective: to find a method of diagnostics of persistent post-traumatic extensor contractures of the knee joint, which hads to surgical treatment. Methods: 23 people were examined with persistent extensor contractures of the knee joint that developed fractures of the femur. Complications were determined in all patients: delayed consolidation or nonunion of bone fragments, osteomyelitis, defects. The range of motion in the knee joint was 0°/0°/10°–15°. It has been established that for some, when the knee joint was bent, the movement ended smoothly, while for others, it was abrupt, with a sonic blow, as an obstacle. This phenomenon was investigated using a developed device consisting of a sound-receiving headset and a recording smartphone with the «Sound Oscilloscope » program. Results: in 14 patients without a «symptom of hitting an obstacle» the range of movements in the knee joint reached normal values within 3–4 months of rehabilitation treatment. In 9 patients with a «symptom of hitting the obstacle», conservative treatment of knee joint contracture proved ineffective. These patients were diagnosed with «persistent extensor contracture of the knee joint» and surgical intervention was performed, after which the mobility in the joint was restored. We have proposed a method for determining the need for surgical treatment with persistent extensor contractures of the knee joint (patent № 132107 UA), which describes the «symptom of hitting an obstacle». Conclusions: the method of determining the need for surgical treatment of persistent extensor contractures of the knee joint, as well as the «symptom of hitting the obstacle» is a diagnostic sign that indicates with a high degree of probability that the patient has the specified pathology. In these patients, it is necessary to immediately perform surgical treatment, without wasting time on a long-term ineffective and costly rehabilitation therapy.